Scaling up orange-fleshed sweetpotato for improved nutrition and food security, Ethiopia. Building institutional support. Project profile. - International Potato Center (International Potato Center, 2019)
In addition to providing vital food security, orange-fleshed sweetpotato is rich in vitamin A, a nutrient that is essential for healthy growth in children. The project promotes its adoption at institutional level to address Ethiopia’s persistent malnutrition.